Association between paternal pre-pregnancy body mass index with preterm birth and low birth weight - Sun, Mengting; Zhang, Senmao; Chen, Letao; Li, Yihuan; Diao, Jingyi; Li, Jinqi; Wei, Jianhui; Song, Xinli; Liu, Yiping; Shu, Jing; Wang, Tingting; Zhu, Ping; et al. (Frontiers in Pediatrics, 2022)
Background With the current global epidemic of obesity, especially among men, there is a need to understand its impact on adverse pregnancy outcomes. This study aimed to assess whether paternal pre-pregnancy body mass index (BMI) was associated with preterm birth and low birth weight in offspring. Methods Multinomial logistic regression model was used to analyze associations between paternal BMI and preterm birth and low birth weight in different subgroups, the final model was adjusted for confounding factors of mothers and fathers. Further subgroup analysis was conducted to explore the stability of the risk associations. Results A total of 34,104 participants were included in this study, including 1,442 (4.2%) underweight, 13,930 (40.9%) overweight and 5,008 (14.7%) obese according to paternal BMI. The total incidence of preterm birth was 11.85% (4041/34104), and the incidence of low birth weight was 8.86% (3020/34104). In the total study population, compared with normal weight men, paternal pre-pregnancy overweight or obese was associated with a significantly increased risk of preterm birth [aOR; 95% CI respectively (1.34; 1.25–1.45 vs. 1.26; 1.14–1.40)] and low birth weight [aOR; 95% CI respectively (1.60; 1.46–1.74 vs. 1.40; 1.25–1.58)] in offspring. The results of subgroup analysis showed that the direction of the risk association was consistent, indicating good stability. Conclusion Paternal pre-pregnancy overweight and obesity were associated with an increased risk of preterm birth and low birth weight in their offspring.